Las dos Españas: terror and crisis in contemporary Spain - Manganas, Nicholas (The Cañada Blanch, Sussex Academic Studies on contemporary Spain, 2016)
Introduction -- Narratives of political violence: the narrative of Las dos Españas and the global metanarrative of terror -- History, terror and myth: ETA, Spain, the state and the nation -- Terror and the state: the GAL, fantasy and the (un)imaginable -- The Aznar years (1996-2004): history, politics and narratives of the Spanish "nation" -- Blame games and narrative battles: the March 11, 2004, "terror" attacks and the March 11 general election -- The Zapatero years (2004-2011): Crispación and the return of Las dos Españas -- The beginning and the end of the ETA peace process (2006-2007): between dialogue and Engaño -- The semantics and rhetoric of victims of terrorism groups -- From terror to crisis -- Conclusion